A Question of Leadership Is the Level of CEO Compensation Reasonable - Jancerak, Melodie; Jancerak, Melodie; Drath, Wilfred (Center for Creative Leadership, 2003)
The evidence that CEO compensation has grown by leaps and bounds over the past twenty years and that the gap between CEO compensation and the pay of the average worker has widened considerably is irrefutable.